Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

Find the point(s) on the ellipse: x²/a² + (y - k)²/b² = 1 where the tangent lines that passes through the point: (m, n)?

NOTE:

seeking a point on the ellipse, not just the tangent line. also (m, n) is an arbitrary point NOT on the ellipse.

Update:

seeking two points (not just one)

+++++++++++++++++++++

Find the points on the ellipse:

x²/a² + (y - k)²/b² = 1

where the tangent lines pass through the point:

(m, n)

2 Answers

Relevance
  • 6 years ago

    Since linear transformations leave incidence properties (and hence tangents) invariant, translate "k" units down, then compress vertically by "1/b" and horizontally by "1/a". That takes the ellipse to a unit circle about the origin, x²+y²=1 and the point (m,n) to (m/a,(n-k)/b)=(M,N). {Note that M²+N²≥1 is the same as m²/a²+(n-k)²/b²≥1.}

    Now look at the similar right triangles formed by the origin O, P(x,y), Q(M,N), and the orthogonal projection of (x,y) on the line from the origin to (M,N), calling that R. A little playing around with similar triangles gives|OM|/|OX|=|OX|/|OR|, and |RX|/|OX| = |MX|/|OM| = √(|OM|²-|OX|²)/|OM|. Since |OX|=1, |OR|=1/|OM| and |RX|=&radic(|OM|²-1)/|OM|. Furthermore, |RX| is (by construction) perpendicular to |OM|, hence it is parallel to (N, -M). Therefore:

            (RX) = ±√(|OM|²-1)/|OM|² (N, -M) = ±√(M²+N²-1)/(M²+N²) (N, -M)

    and

            (OR) = (M, N) ÷ |OM|² = (M, N) / (M²+N²)

    so

            (x,y) = (OR) + (RX) = (M±N√(M²+N²-1), N∓M√(M²+N²-1)) / (M²+N²)

    {Note the requirement that M²+N²≥1. The point (m,n) must be outside the ellipse.}

    Decompressing and then translating up produces the solution to the original problem:

            (x,y) = (aM ± aN√(M²+N²-1),  bN ∓ bM√(M²+N²-1) + k(M²+N²)) ÷ (M²+N²)

            = (m ± (a/b)(n-k)√Δ,  n ∓ (b/a)m√Δ + kΔ) / (Δ+1),   where   Δ = m²/a² + (n-k)²/b² - 1 ≥ 0

    Check my algebra! Even this simplied approach gave me trouble...

    UPDATE: Thanks for showing me your solution! I think I like my solution. In addition to being algebraically easier, this one also works for an ellipse with a horizontal translation (h≠0). In fact, generalizing to the real projective plane, this idea works for any conic. In the projective plane any conic can be transformed to a unit circle with a linear transformation, where the problem is solved with similar triangles and one application of the Pythagorean theorem. The inverse linear transforation gets the desired solutions to the original problem.

    Specifically, for h≠0, we have M=(m-h)/a and N=(n-k)/b, so Δ = (m-h)²/a² + (n-k)²/b² - 1

            x = [ m ± (a/b)(n-k)√Δ + hΔ ] ÷ (Δ+1)

            y = [ n ∓ (b/a)(m-h)√Δ + kΔ ] ÷ (Δ+1)

    Which reduces to your answer in the case h=0.

Still have questions? Get your answers by asking now.